2017
DOI: 10.1123/japa.2015-0122
|View full text |Cite
|
Sign up to set email alerts
|

High-Speed Resistance Training in Older Women: The Role of Supervision

Abstract: Older women participated in a 12-week high-speed resistance training program under two supervisor-to-subject ratio methods (i.e., high versus low supervision) to assess its effects on muscle strength, power, functional performance, and quality of life assessed before (T1) and after (T2) intervention. Women were divided into either the control group (CG, n = 15), high supervision group (HSG, n = 30), or low supervision group (LSG, n = 28). The training program included exercises requiring high-speed concentric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 0 publications
3
31
1
Order By: Relevance
“…However, according to the authors, these results possibly did not represent an effect of training as these responses were similar between the training and the non-training groups (31). Regarding traditional resistance training (e.g., use of slow to moderate movement velocity), previous studies have observed a significant chronic reduction in resting BP in T2DM individuals after exercise interventions (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)26), while other studies did not (33)(34)(35)(36)(37). It is worth noting that most of the studies that observed a significant chronic effect of traditional resistance training on resting BP in T2DM subjects used a higher weekly frequency of training (i.e., three times) (17)(18)(19)22,26,33) and/or longer intervention period (>12 weeks) (16)(17)(18)(19)(20)26,33).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…However, according to the authors, these results possibly did not represent an effect of training as these responses were similar between the training and the non-training groups (31). Regarding traditional resistance training (e.g., use of slow to moderate movement velocity), previous studies have observed a significant chronic reduction in resting BP in T2DM individuals after exercise interventions (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)26), while other studies did not (33)(34)(35)(36)(37). It is worth noting that most of the studies that observed a significant chronic effect of traditional resistance training on resting BP in T2DM subjects used a higher weekly frequency of training (i.e., three times) (17)(18)(19)22,26,33) and/or longer intervention period (>12 weeks) (16)(17)(18)(19)(20)26,33).…”
Section: Discussionmentioning
confidence: 92%
“…It is important to observe that BP reductions are more commonly observed following aerobic training programs and some studies show no chronic BP reductions after resistance exercise on T2DM people (33)(34)(35)(36)(37)46). However, considering that the performance of strength exercises such as MPT is also extremely necessary for older adults, due to documented neuromuscular and functional benefits of these interventions (9-12), it is important to have the knowledge about the possible effects of an MPT on BP besides the neuromuscular and functional benefits that have been already documented (10)(11)(12). Although there was no statistical reduction in resting BP after 12 weeks of MPT, the present study exhibits important clinical perspectives.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All participants were instructed to keep their habitual lifestyle (including eating habits) throughout the intervention. The physical activity level was measured at baseline as previously described26 and was expressed in metabolic equivalents (MET-min/week).…”
Section: Methodsmentioning
confidence: 99%
“…Another mark was positioned at 90% of maximum CMJA height. To ensure that subjects achieved the desired intensity (i.e., jump height) during each jump, a coach-to-subject ratio of 1:1 was used during all training sessions (31). The coach supervised each jump and was attentive to the intensity and technical skill level of the jump.…”
Section: Training Programmentioning
confidence: 99%